A review on Ethno-Botany, Pharmacology and Phytochemistry of Cleome Viscosa Linn. (Cleomaceae): Exploring the medicinal properties and chemical compounds of Cleome viscosa Linn. (Journal of Advances and Scholarly Researches in Allied Education, 2021)
Cleome viscosa Linn. (CLEOMACEAE) is a wild, sticky herb, commonly called “dog mustard”.Traditionally this plant possesses beneficial effects as an antiscorbutic, anthelmintic, antiseptic, febrifugeand cardiac stimulant. A wide variety of phytoprinciples have been isolated from its root, leaves andseeds.